Application of Arrowroot Starch Antimicrobial Edible Coating with Addition of Lemongrass Extract on Strawberry Fruit - Afriyanti Afriyanti; Catur Budi Handayani; Retno Widyastuti (Journal of Food and Agricultural Product, 2021)
Public awareness of the food quality which is they consume is increasing. Food consumption becomes more varied by not only consuming carbohydrates, protein and fat sources, but balanced with the consumption of fruits as a source of vitamins. One way to maintain the quality of fruits during storage is to use edible coatings. Edible coatings made from hydrocolloid materials such as starch as natural coating materials, are non-toxic and safe for health so that starch-based edible coatings are feasible to be developed. One of them is arrowroot starch. Improving the coating function is done by adding antimicrobial ingredients, one of which is lemongrass extract. The purpose of this study was to determine the effectiveness of the use of antimicrobial edible coating on the physica and chemical characteristics of strawberryes during storage. The experimental design used in this study was a factorial completely randomized design, with the treatment of Antimicrobial Concentration (A) with five levels of treatment, namely: A1 = 0%, A2 = 0.1%, A3 = 0.2%; A4 = 0.3% and A5 = 0.4% and Storage Time, namely B1 = 0 days; B2 = 2 days; B3 = 4 days and B4 = 6 days. Each treatment was repeated twice to obtain an experimental unit of 5 x 4 x 2 = 40 experimental units. Product analysis carried out was weight loss, texture and total dissolved solids. Based on the data obtained, the use of antimicrobial concentration and storage time affect the results of the analysis. The longer the storage, the weight loss increased, the texture became softer and the total dissolved solids decreased.Keywords: antimicrobia, arrowroot, edible coating, lemongrass, strawberry